(untitled) (American Journal of Pedagogical and Educational Research, 2022)
This article analyzes the factors influencing the development of pedagogical personnel’s professional competence in the context of educational transformation. It has also been established that international experience and collaboration have a positive impact on the quality of education and the professional growth of teachers. The article presents scientific conclusions on modern pedagogical approaches and their significance in the education system, along with recommendations for improving pedagogical competence.